Pengaruh Strategi Promosi dalam Bauran Pemasaran Terhadap Keputusan Pembelian - Rahmania Utami; Annur Fitri Hayati (Universitas Negeri Padang, 2023)
The aims of this study were to determine how advertising, personal selling, and sales promotion influenced purchasing decisions at Rawit Indah Supermarkets in Pasaman District, West Pasaman Regency. This research approach is a quantitative research with a causative research type. The population of this research is all consumers who have shopped at Rawit Supermarkets. Using purposive sampling technique with a total sample of 97 people. As well, descriptive data analysis techniques and inductive analysis. The result of this research, (1) advertising, personal selling, and sales promotion variables all have a significant effect on purchasing decisions, (2) advertising variables have a significant effect on purchasing decisions, (3) individual sales variables have a significant effect on purchasing decisions, and (4) sales promotion variables have a significant effect on purchasing decisions